ANALISIS KINERJA WARTAWAN SURAT KABAR TIRAS POST DI BANDAR LAMPUNG - Diana Amisani (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2010)
Press as a part of state development components has a duty to support the process ofdevelopment through any kind of spreading out development information, including social control inguiding and educating the community. The development of press in Lampung, in quantitative, hasincreased significantly compared with that of pre reformation era. However; in qualitative, it needsstudying in more specific to asses the positive or negative role which may affect the development ofcommunity’s opinion. To gain a good impression, a press has to be objective and strongly holduniversal values.One of the press publications in Lampung is Surat Kabar Tiras Post . In this daily paper arestill found many weaknesses such as unqualified news, editing products, number and quality ofreleased news, cut off news, double news, faded color, and late in sending news to house ofproduction or editorial staff. All of these weaknesses hinder the editing process and lay-out. Thishappens due to the quality of human resources this paper has and their attempt to increase theirwork quality.This research assesses how much the influence of motivation, discipline, andcommunication to journalist work achievement at the publisher of Tiras Post either simultaneously orpartially. The population in this research is all members of journalist which are 30 people in total. Thenumber of sampling is equivalent with the total of population or it is so called census technique. Theresult of hypothesis test turns out that there is a significant influence—simultaneously or partially—among motivation, discipline, and work communication toward journalist Performance.